KONTRIBUSI INVESTASI ITALIA MELALUI PT. SAIPEM INDONESIA TERHADAP PEREKONOMIAN KARIMUN TAHUN 2010-2012 - Muhamad Zulfri Ramsi; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes contributions of Italian investment through PT. Saipem Indonesia toward economic growh in Karimun District in 2010-2012. Karimun District that has been as created Free Trade Zone (FTZ) and Special Economic Zone (SEZ) created opportunities for Italia to invest in Karimun. Italia investment is poured through PT. Saipem Indonesia that was established on May 31st 2011 in Karimun District. Operation of PT. Saipem Indonesia in Karimun District increased economic growth in Karimun district.The writer collects data from journals, books, thesis, reports, working papers, tabloids, encyclopedia, and online media to analyze the contribution of Italia investment through PT. Saipem Indonesia in Karimun. The theoretical framework applied in this research are neoliberalism perspective from David Harvey, international investment theory from Kindley Berger and monopolistic advantages theory from Stephen Hymer.The research shows that contribution of Italia investment through PT. Saipem Indonesia provided great contributions, started from development of company project until established and company operation. Those contribution are high standard of employees salary, Saipem Externalities Local Content Evaluation (SELCE) method, economic value in development project, recruitment of local employee, young graduates program, training center, contributions in health sector, school and transfer of knowledge for student and society in Karimun District. These contributions influence to Regional Gross Domestic Product Karimun District, increase economic growth, increase Employees Participation Rates and decreased unemployment rates in Karimun District.Key words: PT. Saipem Indonesia, contribution, investment, economic growth, employees.